2016
DOI: 10.1037/spy0000056
|View full text |Cite
|
Sign up to set email alerts
|

Effects of anxiety on anticipation and visual search in dynamic, time-constrained situations.

Abstract: We tested the predictions of Attentional Control Theory (ACT) by examining how anxiety affects visual search strategies, performance efficiency, and performance effectiveness using a dynamic, temporal-constrained anticipation task. Higher and lower skilled players viewed soccer situations under 2 task constraints (near vs. far situation) and were tested under high (HA) and low (LA) anxiety conditions. Response accuracy (effectiveness) and response time, perceived mental effort, and eye-movements (all efficienc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
28
2
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 36 publications
(115 reference statements)
5
28
2
1
Order By: Relevance
“…Empirical findings point to the influence of emotions on various aspects of sports performance. For example, studies found that anxiety prolonged response times (Vater, Roca, & Williams, 2015), impaired attention regulation (Englert, Zwermmer, Bertrams, & Oudejans, 2015), https://doi.org/10.1016/j.psychsport.2018.11.004 Received 7 August 2018; Received in revised form 19 October 2018; Accepted 6 November 2018 and decreased perceptual-motor performance (i.e., dart throwing; Englert, Zwemmer, Bertrams, & Oudejans, 2015). In contrast, happiness improved power and speed performance (Rathschlag & Memmert, 2013 and predicted more successful game involvement (i.e., in basketball; Uphill et al, 2014).…”
Section: Emotions In Sportsmentioning
confidence: 99%
“…Empirical findings point to the influence of emotions on various aspects of sports performance. For example, studies found that anxiety prolonged response times (Vater, Roca, & Williams, 2015), impaired attention regulation (Englert, Zwermmer, Bertrams, & Oudejans, 2015), https://doi.org/10.1016/j.psychsport.2018.11.004 Received 7 August 2018; Received in revised form 19 October 2018; Accepted 6 November 2018 and decreased perceptual-motor performance (i.e., dart throwing; Englert, Zwemmer, Bertrams, & Oudejans, 2015). In contrast, happiness improved power and speed performance (Rathschlag & Memmert, 2013 and predicted more successful game involvement (i.e., in basketball; Uphill et al, 2014).…”
Section: Emotions In Sportsmentioning
confidence: 99%
“…Only a few studies have attempted to understand how visual fixations in football vary as a consequence of different task constraints (i.e., distance to the ball, attack v defense, number of players, and viewing perspective). For example, studies of simulated 11 v 11 play have shown that the number of fixations increases, the duration of fixations decreases, and the location of fixations is directed toward more objects of information when the ball is far from the player (Roca et al, 2013;Vater et al, 2016). When the ball travels closer, the location of gaze becomes more centrally focused toward the player in possession (PiP; Roca et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Some studies portrayed the empirical practices on how the martial arts athletes experienced with some influential factors when they compete in the various matches through the amateur and professional caliber. [20] stressed that athletes' anxiety increased since the higher state anxiety ratings led to decreased athletes' performance efficiency because the responding times and mental effort increased, too. Anxiety influenced towards search strategies with the higher skilled athletes who performed in the various matches, as compared with lower skilled ones.…”
Section: Introductionmentioning
confidence: 99%